THU0238 A Randomized, Double-Blind, Placebo-Controlled, 16-Week Study of Subcutaneous Golimumab in Patients with Active Nonradiographic Axial Spondyloarthritis. (9th June 2015) - Sieper, J.; van der Heijde, D.; Dougados, M.; Maksymowych, W.P.; Boice, J.A.; Bergman, G.; Curtis, S.; Tzontcheva, A.; Huyck, S.; Weng, H.H.
Abstract : Background: Axial spondyloarthritis (axSpA), including ankylosing spondylitis (AS) and nonradiographic axial SpA (nr-axSpA), is a chronic inflammatory disease marked by back pain and progressive spinal stiffness. Objectives: To determine whether golimumab (GLM) is superior to placebo (PBO) in patients with nr-axSpA. Methods: GO-AHEAD was a double-blind, randomized, PBO-controlled trial of GLM in patients with active nr-axSpA (ASAS criteria and centrally read sacroiliac [SI] joint X-rays and MRIs, disease duration ≤5 years, chronic back pain, high disease activity [total back pain ≥40 mm on a 0–100 mm VAS and BASDAI ≥4 cm], and inadequate response/intolerance to NSAIDs). Patients were randomized 1:1 to SC GLM 50 mg or PBO every 4 wks. The primary endpoint was ASAS 20 at wk 16. Treatment group differences for all patients and those with objective signs of inflammation (OSI; baseline inflammation by centrally evaluated SI MRI and/or elevated CRP) were compared by stratified Miettinen–Nurminen method for responder endpoints and Mann–Whitney test for SPARCC MRI SI score. Results: Of 198 patients enrolled, 197 were treated (GLM=97, PBO=100). Mean age was 31 years; 57% were male. At baseline, mean BASDAI was 6.5 cm (SD=1.5); SPARCC MRI SI, 11.3 (SD=14.0); and ASDAS, 3.5 (SD=0.9). The primary endpoint (wk 16 ASAS 20) was achieved by more GLM patients than PBO patients (71.1% vs 40.0%, P <.0001; table ). More GLM than PBO patients attained ASAS 40, ASAS partial remission, and BASDAI 50 (table ). Mean ASDAS improvements were greater with GLM (−1.7) than PBO (−0.6; P <0.0001). Similar results were obtained in the OSI population for all clinical measures. In the non-OSI population, wk 16 ASAS 20 attainment was comparable between treatments (47.4% GLM vs 50.0% PBO; P =.8711); effects of GLM on other endpoints were small or nonexistent. Mean SPARCC MRI SI score improvements were greater with GLM than PBO for all patients (−5.3 vs −0.9; P <0.0001) and the OSI population (−6.4 vs −1.2, P <0.0001). Adverse events (AEs) were reported in 41% of GLM and 47% of PBO patients. Serious AEs were reported in 1 GLM patient (female partner reported fetal death) and 2 PBO patients (cholelithiasis, back pain). No serious infections, serious opportunistic infections, active tuberculosis, malignancies, serious systemic hypersensitivity, or deaths were reported. Conclusions: Patients with active nr-axSpA treated with GLM had significantly greater improvements in disease activity and inflammation on MRI than patients treated with PBO. GLM was generally well tolerated. Disclosure of Interest: J. Sieper Consultant for: AbbVie, Eli-Lilly, Janssen Biologics, Merck, Novartis, Pfizer, Roche, UCB, D. van der Heijde Consultant for: AbbVie, Amgen, AstraZeneca, Augurex, BMS, Boehringer Ingelheim, Celgene, Centocor, Chugai, Covagen, Daiichi, Eli-Lilly, Galapagos, GSK, Janssen Biologics, Merck, Novartis, Novo-Nordisk, Otsuka, Pfizer, Roche, Sanofi-Aventis, UCB, Vertex, Employee of: Imaging Rheumatology BV, M. Dougados Grant/research support from: AbbVie, Lilly, Novartis, Pfizer, Roche, Sanofi, UCB, Consultant for: AbbVie, Lilly, Novartis, Pfizer, Roche, Sanofi, UCB, W. Maksymowych Grant/research support from: AbbVie, Janssen, Pfizer, Consultant for: AbbVie, UCB, Pfizer, Merck, Janssen, Eli Lilly, Celgene, Synarc, J. Boice Employee of: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ (former), G. Bergman Employee of: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, S. Curtis Employee of: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, A. Tzontcheva Employee of: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, S. Huyck Employee of: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, H. Weng Employee of: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ (former)